Mild and selective hydrogenation of nitriles into primary amines over a supported Ni catalyst. (12th December 2019) - Wang, Jianjian; Tang, Qingjie; Jin, Shiwei; Wang, Yanxin; Yuan, Ziliang; Chi, Quan; Zhang, Zehui
Abstract : The mesoporous Al2 O3 supported Ni catalyst demonstrated a high activity and selectivity for the hydrogenation of nitriles into primary amines under the mild conditions (60–80 °C and 2.5 bar H2 ) with ammonia as the additive. Abstract : The development of new heterogeneous non-noble catalytic systems for the selective hydrogenation of nitriles into primary amines is a challenging task. In this study, a mesoporous Al2 O3 supported Ni catalyst (denoted as Ni/Al2 O3 -600, where 600 represents the reduction temperature) demonstrated a high catalytic activity for the hydrogenation of nitriles under mild conditions (60–80 °C and 2.5 bar H2 ) with ammonia as the additive. This catalytic system has a wide substrate range and the Ni/Al2 O3 catalyst demonstrated a good tolerance to other functional groups, which was possibly due to its high catalytic activity under mild conditions. A plausible reaction pathway was proposed for the hydrogenation of nitriles into primary amines, and it was found that ammonia played a great role in the enhancement of the selectivity of primary amines by the inhibition of the side reaction to generate secondary amines. In addition, the Ni/Al2 O3 -600 catalyst could be reused five times without activity loss through convenient magnetic recovery.